Software development for forest growth models and management. CORKFITS: web based growth simulator - Surový, Peter (2011)
New methods of forest management and the study of their impact on sustainability are strongly dependent on realistic mathematical modelling. The complexity of the models however, makes the use of computational power, and thus the incorporation of knowledge from computer science and research, indispensable. In this paper we wish to demonstrate the development of a simulator for the growth and production of cork oak woodlands – montados. The software is divided into three sub-modules, sharing a common core, with functions and mathematical operations. The desktop client allows for repeated operations for more intense calculations, and statistical operations for modelling purposes. The web version is intended to be used by final users in forest practice. It permits simulation of inventory data based on individual tree measurements, and inventory data based on plot description with a reduced amount of detail (number of trees per ha, diameter structure, etc.) The last module allows the incorporation of the cork model into other software by means of SOAP protocol, via web services. It conforms to the WS-I Basic Profile 1.1, to ensure interoperability among the largest number of clients. This module allows other developers to use the cork oak growth-model in their software, and the developers from other areas of expertise (management optimisation, decision support...) have the opportunity to test their techniques on real stands, with the most recently-updated model versions.